2016
DOI: 10.1007/s00330-016-4563-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis to determine the contribution of mr imaging to the diagnosis of foetal brain abnormalities In Utero

Abstract: ObjectivesThis systematic review was undertaken to define the diagnostic performance of in utero MR (iuMR) imaging when attempting to confirm, exclude or provide additional information compared with the information provided by prenatal ultrasound scans (USS) when there is a suspicion of foetal brain abnormality.MethodsElectronic databases were searched as well as relevant journals and conference proceedings. Reference lists of applicable studies were also explored. Data extraction was conducted by two reviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 49 publications
3
43
1
2
Order By: Relevance
“…There are great controversies regarding the prenatal US versus MRI, as Wagenvoort et al [10] stated that foetal brain MRI added more information and is more accurate than foetal US. Additionally, Jarvis et al [11] concluded that when foetal brain abnormalities are suspected on US, MR imaging can significantly contribute to the diagnostic pathway by clarifying findings and significantly increasing the detection rate of abnormalities, particularly in the midline and posterior fossa anomalies. However, dedicated neuro-sonography studies concluded that MRI is for the confirmation of diagnosis and that each modality provided additional/different information only in a minority of cases [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are great controversies regarding the prenatal US versus MRI, as Wagenvoort et al [10] stated that foetal brain MRI added more information and is more accurate than foetal US. Additionally, Jarvis et al [11] concluded that when foetal brain abnormalities are suspected on US, MR imaging can significantly contribute to the diagnostic pathway by clarifying findings and significantly increasing the detection rate of abnormalities, particularly in the midline and posterior fossa anomalies. However, dedicated neuro-sonography studies concluded that MRI is for the confirmation of diagnosis and that each modality provided additional/different information only in a minority of cases [12].…”
Section: Discussionmentioning
confidence: 99%
“…There is now considerable evidence supporting the value of fetal MRI in diagnosing fetal brain abnormalities, based on systematic reviews and our prospective study. Whilst designing the MERIDIAN study, fetal medicine focus groups were formed with the purpose of identifying important issues that should be addressed by the study in order to improve clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…There was, however, accumulating evidence from MRI studies before the start of the MERIDIAN study suggesting that the diagnosis of agenesis of the CC on ultrasound may not be straightforward. Most publications comparing ultrasound and MRI of the fetal brain from that period described CC pathology as the greatest source of discrepancy between ultrasound and MRI reports and this has been highlighted in systematic reviews and meta‐analyses. In addition, a recent publication from our group based on the experience of 7 years of MRI studies immediately before the start of the MERIDIAN study raised serious questions about the ability of ultrasound to diagnose failed commissuration.…”
Section: Discussionmentioning
confidence: 99%